HASHTAG SEBAGAI ALAT PENYEBARAN DAKWAH DIGITAL AKUN TIKTOK @SWARGALOKA.3578 TERHADAP PROGRAM KERJA LONTONG KUPANG DALAM EDUKASI TERTIB ADMINISTRASI KEAGAMAAN - Ulfa Safira; Hafidlatul Fauzuna (NIVEDANA : Jurnal Komunikasi dan Bahasa, 2026)
Hashtags (#) are metadata used in various social media today. Chris Messina was the first user on Twitter in 2007 for the news category. As social media develops, the use of hashtags has now spread to educational content, vlogs, da'wah, and government program socialization. This study discusses the use of hashtags as a new medium in digital da'wah on the TikTok platform @swargaloka.3578 as a means of educating religious administration through the "Lontong Kupang" program in Surabaya City. This research method uses a qualitative method with a netnographic approach. Data were analyzed using a content analysis design on the uploads of the @swargaloka.3578 account as the research object. Primary data were obtained through digital observation, screenshots, and in-depth content analysis. Secondary data include books, scientific journals, interviews with TikTok managers from the Surabaya City Population and Civil Registration Office, as well as supporting theories such as the theory new media and the theory of diffusion of innovation. Meanwhile, tertiary data are in the form of statistical reports or insights into video distribution. The research findings show that hashtag use plays a central role in increasing reach and engagement with digital outreach programs on religious administration education. Through appropriate hashtags, the "Lontong Kupang" program can be more widely disseminated as a transformative form of public service implementation. Therefore, while hashtags are an influential technical indicator, successful education still requires thorough content distribution analysis and educational messaging to ensure the information transformation is well-received by the public.